A STUDY OF ADSORPTION OF DAZOMET FROM AQUEOUS SOLUTION ON KAOLIN - Ali, Inam Hussein (Al-Nahrain Journal of Science, 2009)
In this research, the adsorption of dazomet from aqueous solution on kaolin at (30 C˚) was studied. It was observed that the adsorption was consistent with the Freundlich adsorption isotherm and thus it is evident that the multilayer adsorption takes place from solutions. The adsorption phenomena were investigated with respect to change in concentration, and duration of process. The adsorption rate of dazomet was found to fit the first- order of kinetic equation. Also, the adsorption rate decreased linearly with the initial concentration which evident that the adsorption is controlled by a film diffusion mechanism.